STUDY OF THE THERMAL STABILITY OF BARNASE PROTEIN MUTANTS WITH MOLKERN SOFTWARE - E. S. Fomin; N. A. Alemasov (Вавиловский журнал генетики и селекции)
A thermal stability study of several barnase mutants has been carried out by the λ dynamics method. The method has been implemented in the MOLKERN software package. Mutations of amino acids with non-zero charge are chosen for the study, because in this case λ dynamics gives results differing dramatically (> 10 kJ/mol) from experimental data in nearly one-fourth of cases. A new modification of λ potentials is proposed, which takes into account charge changes, as well as the Net-Q method, in order to obtain reliable charge distributions for charged amino acids. The results obtained for the R72G mutation show a better agreement with experimental values than the results of other authors.